2003
DOI: 10.1144/gsl.mem.2003.020.01.71
|View full text |Cite
|
Sign up to set email alerts
|

The Tyne Gas Fields, Block 44/18a, UK North Sea

Abstract: The Tyne Fields, operated by ARCO British Limited, are located within UKCS Block 44/18a, situated 180 km off the Yorkshire coast in a water depth of 65 ft. The fields comprise three separate accumulations, each with a different gas-water contact and varying gas compositions, which are known as Tyne North, Tyne South and Tyne West. The three accumulations are combined structural and stratigraphical traps. The reservoir sandstones are of the Lower Ketch member of the Schooner Formation and are Carboniferous West… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 6 publications
0
0
0
Order By: Relevance
“…Thicknesses of the Ketch Formation range from approximately 100 m to approximately 400 m (Conway and Valvatne, 2003;Moscariello, 2003;O'Mara et al, 2003a;Dredge and Marsden, 2020;Huis in't Veld et al, 2020;Moscariello and Goffey, 2020), and it shows a general southwesterly thickening with the thickest intervals preserved in the Schooner and Ketch fields. Detailed field studies have demonstrated that the sandstones were deposited by a northeast-to-southwest-flowing, braided fluvialdeltaic system draining emergent areas of the Mid North Sea high and Rinkobing-Fyn high (Morton et al, 2005).…”
Section: Controls On Carboniferous Carbon Storage Play Fairwaysmentioning
confidence: 97%
“…Thicknesses of the Ketch Formation range from approximately 100 m to approximately 400 m (Conway and Valvatne, 2003;Moscariello, 2003;O'Mara et al, 2003a;Dredge and Marsden, 2020;Huis in't Veld et al, 2020;Moscariello and Goffey, 2020), and it shows a general southwesterly thickening with the thickest intervals preserved in the Schooner and Ketch fields. Detailed field studies have demonstrated that the sandstones were deposited by a northeast-to-southwest-flowing, braided fluvialdeltaic system draining emergent areas of the Mid North Sea high and Rinkobing-Fyn high (Morton et al, 2005).…”
Section: Controls On Carboniferous Carbon Storage Play Fairwaysmentioning
confidence: 97%